2019
DOI: 10.5194/isprs-archives-xlii-2-w9-663-2019
|View full text |Cite
|
Sign up to set email alerts
|

The Suitability of Terrestrial Laser Scanning for Building Survey and Mapping Applications

Abstract: <p><strong>Abstract.</strong> The popularity of Terrestrial Laser Scanner (TLS) has been introduced into a field of surveying and has increased dramatically especially in producing the 3D model of the building. The used of terrestrial laser scanning (TLS) is becoming rapidly popular because of its ability in several applications, especially the ability to observe complex documentation of complex building and observe millions of point cloud in three-dimensional in a short period. Users of buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…This analysis was conducted for each investigated building by means of the M3C2 algorithm implemented into the free software CloudCompare (https://www.danielgm.net/cc/ -last access 05/10/2022). In performing this analysis, we chose the 3D point-cloud derived from the TLS survey as a reference because of its widely recognised reliability (Rodríguez-Martín et al, 2019;Russhakim et al, 2019)…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…This analysis was conducted for each investigated building by means of the M3C2 algorithm implemented into the free software CloudCompare (https://www.danielgm.net/cc/ -last access 05/10/2022). In performing this analysis, we chose the 3D point-cloud derived from the TLS survey as a reference because of its widely recognised reliability (Rodríguez-Martín et al, 2019;Russhakim et al, 2019)…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…For example, terrestrial laser scanners (TLS) are marked by the high level of accuracy and detail they provide. However, their utilization at large-scale sites can be time-consuming and cumbersome, thereby limiting their productivity (Russhakim et al, 2019). In contrast, the utilization of portable laser scanners (PLS), mostly handheld, is characterized by their lower resolution and noisy responses.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the utilization of portable laser scanners (PLS), mostly handheld, is characterized by their lower resolution and noisy responses. They facilitate, though, an efficient survey of large-scale sites, making their application attractive (e.g., Russhakim et al, 2019;Patrucco et al, 2019;Bronzino et al, 2019). In that respect, Russhakim et al (2019) reported that three persons and 60 min.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scope of application of PMMSs is diverse: from cultural heritage constructions [13] and civil structures to industrial sites [14], indoor spaces [15], and natural environments [16]. PMMSs contain two groups of sensors that act in a synchronized way to reconstruct the scene three-dimensionally: navigation and remote sensing modules.…”
Section: Introductionmentioning
confidence: 99%